The health locus of control and health behaviours declared by students of health sciences - Deluga, Alina; Bogdańska, Paulina; Dobrowolska, Beata; Ślusarska, Barbara; Bartoszek, Agnieszka; Szczekala, Katarzyna (Nursing in the 21st Century, 2018)
THE HEALTH LOCUS OF CONTROL AND HEALTH BEHAVIOURS DECLARED BY STUDENTS OF HEALTH SCIENCESIntroduction. Health locus of control is an essential factor affecting lifestyle which plays a major role in choosing health behaviours by individuals including young ones.Aim. The aim of the study was the determination of selected conditions of health control and health behaviours in students of health sciences.Material and methods. The study encompassed 175 students of health sciences at the Medical University of Lublin. The multidimensional health locus of control scale (MHLC), version B, by Z. Juczyński was applied as it measures expectations in three dimensions of health control: internal, external (influence of others) and chance. A special authors’ questionnaire compiled for thepurpose was used to assess health behaviours. Results. The results of the study show that the internal dimension of health control (25.86 points) has the greatest impact on health in the group studied. The oldest study participants dwelling in the countryside gave this dimension a higher ranking than other study participants. For the students health behaviours included fastening seat belts, healthy nutrition and doing sports.Conclusions. The internal dimension of health control constitutes an essential factor determining health behaviours of the study participants. The students who are not able to assess whether they are healthy individuals, significantly more frequently perceive the greatest influence of others on their health.